2008
DOI: 10.1111/j.1365-2672.2008.03884.x
|View full text |Cite
|
Sign up to set email alerts
|

Invasion and intracellular survival ofHafnia alveistrains in human epithelial cells

Abstract: Aims:  The aim of this study was to investigate the invasion and intracellular survival of different Hafnia alvei strains in HeLa cells. Methods and Results:  We performed different experiments on the bacterial invasion of different strains of H. alvei into the HeLa cell line using gentamicin protection assays and immunofluorescence. We also report the time course of cell internalization and the effects of inhibitors on the invasion of H. alvei. Levels of invasion varied depending on the conditions (strain, ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
3
7
0
Order By: Relevance
“…The maximum invasion efficiency observed in the present study is lower than showed by Brucella 24 and Salmonella 18 but similar or higher than those reported in Campylobacter, 2,10 Burkholderia, 17,26 Hafnia alvei, 21 and Prevotella. 8 In the time-course analysis, at .…”
Section: 25supporting
confidence: 85%
See 1 more Smart Citation
“…The maximum invasion efficiency observed in the present study is lower than showed by Brucella 24 and Salmonella 18 but similar or higher than those reported in Campylobacter, 2,10 Burkholderia, 17,26 Hafnia alvei, 21 and Prevotella. 8 In the time-course analysis, at .…”
Section: 25supporting
confidence: 85%
“…21 After pre incubation, the mixture at MOI 100 was used to infect the ovine cells as described previously for the invasion assay.…”
Section: Invasion and Adherence Assaysmentioning
confidence: 99%
“…Recent studies showed that some H. alvei strains were able to enter and persist in human epithelial cells, but little is known about factors contributing to this invasion strategy ( 18 ). Thus, H. alvei lipid A structure elucidation and the identifi cation of hepta-acylated variant among other forms of H. alvei lipid A are important for the understanding of the pathogenicity of this bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…Because the majority of clinical symptoms of diseases caused by this bacterium have LPS-related origin and the lipid A structure predominantly affects the biological activity of endotoxins, it seems to be a gap in our knowledge of H. alvei LPSs. Moreover, recent studies on the invasion and intracellular survival of different H. alvei strains in a HeLa cell line revealed that these bacteria were able to enter and persist in human epithelial cells ( 18 ). For Gram-negative bacteria that employ intracellular survival mechanism during invasion, e.g., Salmonella typhimurium ( 19,20 ), various lipid A modifi cations are needed.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…However, solid evidence supporting the fact of the species being the sole cause of gastrointestinal infection, and whether it could be acquired via food is yet to be found. Several groups have attempted to investigate the possible pathogenesis pathways of H. alvei via biochemical and in vitro approaches [5-7]. However, the molecular basis of the mechanisms has not yet been demonstrated.…”
Section: Introductionmentioning
confidence: 99%